Biomimetic and Biohybrid Systems 5th International Conference, Living Machines 2016, Edinburgh, UK, July 19-22, 2016. Proceedings - Lepora, Nathan F.; Mura, Anna; Mangan, Michael; Verschure, Paul F.M.J; Desmulliez, Marc; Prescott, Tony J. (Lecture Notes in Artificial Intelligence, 2016)
This book constitutes the proceedings of the 5th International Conference on Biomimetic and Biohybrid Systems, Living Machines 2016, held in Edinburgh, UK, in July 2016. The 34 full and 27 short papers presented in this volume were carefully reviewed and selected from 63 submissions. The theme of the conference encompasses biomimetic methods for manufacture, repair and recycling inspired by natural processes such as reproduction, digestion, morphogenesis and metamorphosis.